Physiotherapists` knowledge of the transmission and prevention of communicable diseases - L. Grobler; N. Kleynhans; A. Lubbe; T. Smit; C. Retief; D. Victor; C. J. Bester (AOSIS, 2003)
With the world-wide increase of communicable diseases, adequate knowledge by health professionals of the transmission and prevention of these diseases is essential to ensure effective protection.  The aim of this study was to determine whether practising physiotherapists' knowledge of the transmission and prevention of tuberculosis, hepatitis A, hepatitis B, hepatitis C and HIV/AIDS was adequate to ensure effective protection.A descriptive study was conducted.  One hundred and forty six practising physiotherapists in the Free State received questionnaires on which they had to indicate the relevant transmission and preventative measures for each disease. One hundred and three (70.5%) questionnaires were returned.  Points were allocated for the knowledge of transmission and preventative measures.  The medians with respect to transmission were: tuberculosis 83%, hepatitis A 58%, hepatitis B 67%, hepatitis C 75% and HIV/AIDS 92%.  The medians with respect to preventative measures were: tuberculosis 57%, hepatitis A 58%, hepatitis B 77%, hepatitis C 67% and HIV/AIDS 71%.  The knowledge of transmission was better than the knowledge of preventative measures.  An increase in the knowledge of practising physiotherapists in the Free State is needed to ensure their maximal protection against communicable diseases.